Cálcio e paratormônio séricos na detecção precoce do hipoparatireoidismo pós-tireoidectomia total - Tunes, Roberto Santos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Introdução: As concentrações séricas pós-operatórias de cálcio (Ca) ou paratormônio (PTH) têm sido aventadas como preditoras de hipoparatireoidismo após tireoidectomia total (TT). Porém, ainda não foram estabelecidos padrões mundialmente aceitos para tal fim. Objetivos: Identificar precocemente o hipoparatireoidismo pós-operatório, em pacientes submetidos à TT, por meio da dosagem de Ca e PTH séricos nas primeiras 24 horas após a cirurgia. Casuística e Métodos: Foram estudados, prospectivamente, 76 pacientes operados entre 2013 e 2014. Foram dosados Ca sérico na véspera, durante a TT, com 1, 8, 14 e 24 horas (h) de pós-operatório (PO), e PTH antes, durante, com 1 e 8h PO. Os pacientes foram reavaliados com 7, 30 dias e com 6 meses PO e classificados como: sem hipoparatireoidismo (SH), com hipoparatireoidismo temporário (HT) ou com hipoparatireoidismo permanente (HP). Resultados: 40 pacientes (52,6%) foram incluídos no SH, 24 (31,6%) no HT e 12 (15,8%) no HP. O sexo feminino foi mais prevalente nos três grupos [SH: 85%; HT: 91,7%; HP:100%; p<0,05], e apresentou maior risco para HP [risco relativo (RR)=1,14 (IC 95%:1,04-1,25)]. As curvas de Ca mostraram padrão descendente em todos os grupos, mais acentuado no HP (p<0,05), com slope significativo para os grupos a partir das 8h (p<0,05). Com 24h PO, slope negativo de Ca maior que 10% determinou maior risco para HT [RR=2,00 (IC 95%:1,05-3,18)], enquanto que slope negativo maior que 20% se associou a maior risco de HP [RR=3,89 (IC 95%:1,42-7,47)]. O PTH apresentou queda dos valores absolutos já durante a TT (G3>G2>G1; p<0,05). Com 8h, a média percentual de queda do PTH foi de 100% para os casos com HP (p<0,01). Slope negativo do PTH maior que 75% associou-se a maior risco de HT [RR=2,24 (IC 95%:1,16-3,42), PTH durante a TT; RR=2,24 (IC 95%:1,16-3,42), com 1h; e RR=3,07 (IC 95%:1,82-4,57), com 8h], enquanto que slope negativo maior que 90% aumentou o risco para HP [RR=3,16 (IC 95%:1,18-6,86), PTH durante a cirurgia; RR=22,40 (IC 95%:3,07-160,14), com 1h; e RR=14,00 (IC 95%:3,35-55,98), com 8h]. Queda >6% do Ca em 24h associado a queda do PTH >70% em 1 h ou 36% em 8h apresentou sensibilidade combinada de 94% e 97% para predição de hipocalcemia. Valores de Ca 8,4 mg/dL em 24h associados a PTH 15,6 pg/mL em 1h predizem hipocalcemia com sensibilidade de 94% e especificidade de 68%. Quedas mais acentuadas (93%) do PTH, associadas a Ca 8,4mg/dL mostraram sensibilidade de 100% e especificidade de 80% para HP. Conclusões: As dosagens de Ca e PTH séricos nas primeiras 24 horas após TT foram preditoras de hipoparatireoidismo. Os valores absolutos e a variação percentual negativa do Ca maior que 10% e do PTH maior que 75% nas primeiras 24h, quando comparados aos valores basais, aumentaram o risco para HT, enquanto que reduções de Ca maiores que 20% e de PTH maiores que 90%, aumentaram o risco para HP.

This study aimed to evaluate the production, physical-chemical characteristics, and the application of betalains derived from beetroots (Beta vulgaris L.) microencapsulated by spray drying using carrier agents. Initially, we assessed the influence of process conditions (temperature and drying air flow-rate, concentration and formulation of carrier agents) on the water content of the microcapsules, process yield, solubility, betalain retention and color parameters through a central composite design 24. Particles were produced using blends of two carrier agents: maltodextrin 10 DE (Md) and modified corn starch (Am). Taking into account the results of the experimental design, a group of four samples was selected to be further evaluated regarding morphology, particle size distribution, sorption isotherms, antioxidant activity, glass transition temperature and stability to light and pH. In addition, these samples were applied as natural colorant in a model formulation of petit Suisse cheese, which was subjected to sensory evaluation for acceptance and purchase intention along with a sample of the corresponding commercial product. In all the production trials, the microcapsules presented low water content values (0.16 to 2.91%) and high solubility (> 90%). The yield ranged from 2.96 to 81.34%, and betalain retention in the microcapsules ranged between 40 and 46%. Samples with higher total carrier concentration resulted in larger particles and smoother walls, which are related to increased viscosity of the mixture to be dried; further, they were more stable under light exposure, presenting lower color changes up to 98 days of study. The encapsulation process provided high protection to the antioxidant compounds of betalains, keeping more than 70% of the activity in these samples when compared to the results obtained for the pure extract. The highest antioxidant activity was observed in capsules with higher amount of modified starch in the formulation, as opposed to the glass transition temperature that showed higher values, thus more convenient, for the samples containing more maltodextrin, which demonstrated the protective role of these carrier agents when used together. With respect to pH, microencapsulated samples were more stable than the liquid extract, with preservation of the color, particularly at pH 8, at which there was an evident browning in the extract. The capsules also remained stable regarding color parameters in a wider range of pH when compared to the pure extract. The particles showed low hygroscopicity and the best mathematical adjustment for the sorption isotherms was obtained by the BET model. In the sensorial analysis of petit Suisse cheese, the samples containing beet extract microcapsules as a natural dye obtained answers that were in the majority among "I would probably buy" and "I doubt whether I would buy or not" the product displayed. The samples with the best purchase expectation were those containing the capsules with higher carrier content, which also obtained the highest scores in relation to the color attribute in the acceptance test.
Serum calcium and parathyroid hormone in early detection of post total thyroidectomy hypoparathyroidism
Keywords: Hipocalcemia; Hipoparatireoidismo; Paratormônio; Cálcio; Tireoidectomia